Insecticidal efficacy of Adenocalymma alliaceum extracts against cowpea weevils callosobruchus maculatus (F) stored Vigna unguiculata (L.): Life Sciences-Biotechnology for prospective medical science - GC, Kavitha; D, Poornima (International Journal of Life Science and Pharma Research, 2021)
Insecticidal activities of dried leaf powder and extracts (aqueous and methanol) of Adenocalymma alliaceum Miers, were assessed against Callosobruchus maculatus with a traditional grain storage insecticide Actellic 2% dust. For each sample, 100 g of cowpea seeds were mixed with respective plant preparation and about 25 adults of Callosobruchus maculatus were placed out in a randomized design with three replicates. All three test samples include powder, aqueous and methanolic extracts with irrespective concentration, providing a significant (P<0.05) increase in mortality of adult insects. High concentration aqueous extract exhibited a high reduction of bruchid survival and showed a maximum mortality rate of 90.67% followed by leaf powder (85.33%), and methanol extract (78.67%). The aqueous extract was found to be more effective than the methanol extract and plant powder, though it was not as effective as Actellic 2% dust. Further the LC10, LC50 and LC95 values for the aqueous extract against C. Maculatus unveiled through Probit analysis was 0.101g/100g,1.23g/100g and 30.4g/100g respectively followed by plant powder (LC10=0.199g/100g, LC50= 5.37g/100g and LC95=48.97g/100g) and methanol extract (LC10=0.986g/100g, LC50=2.34g/100g and LC95=56.23g/100g). From the results it was evident that the aqueous extracts of A. alliaceum exhibit highly toxic effects on C. maculatus than that of plant leaf powder and methanol extracts of the A. alliaceum. Consequently, from the study it was obvious that all the tested materials (plant leaf powder, aqueous and methanol extract) of A. alliaceum evaluated were found to have potential insecticidal properties and are capable of protecting stored cowpea against C. maculatus. Thus, this medicinal plant can be used as an environment- friendly product for inhibition of bruchid pests during the storage of cowpeas.